FRI0125 Disease activity is associated with sclerostin levels and (hand and femoral) bone mineral density in patients with established rheumatoid arthritis. (23rd January 2014) - Bernardes, M.; Vieira, T.; Terroso, G.; Aleixo, A.; Madureira, P.; Vieira, R.; Bernardo, A.; Pimenta, S.; Gonçalves, C.; Oliveira, A.; Faria, T.; Martins, M.J.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is associated with localized bone loss in the hands, as well as generalized osteoporosis. Joint erosions are the hallmark of RA. They are caused by an increased bone resorption and the RANKL/OPG system is the main regulator of osteoclast recruitment. In RA there is also no increased bone formation to prevent or heal these erosions. The Wnt pathway has a main role in the control of bone formation through regulation of osteoblast activity. Sclerostin and Dkk-1 are important regulators of this pathway. Objectives: To determine the degree of association of disease activity with bone markers and bone mineral density (BMD) at different anatomical sites in patients with established RA, analyzing the differences according to therapy regimens (conventional DMARDs, exclusively, versus biologics, with or without conventional DMARDs). Methods: Clinical caracteristics and blood samples were collected in a monitoring visit. Portuguese version of the Standford Health Assessment Questionnaire (HAQ), Disease Activity Score four variables (DAS28(4v)), 68 tender and 66 swollen joint counts were obtained. BMD was evaluated by DXA at the lumbar spine, total hip, femoral neck, Wards triangle, hands and second proximal phalanges. We measured ESR and CRP, serum β-C-telopeptide of collagen1 cross-links (β-CTX1), osteocalcin, Dkk-1 (ELISA, Biomedica), sclerostin (ELISA, TECOmedical), RANKL (ELISA, Cusabio), osteoprotogerin (ELISA, Biomedica) and serum serotonin (ELISA, Labor Diagnostika Nord). PASW Statistics 18 was used for statistical analysis. Results: We evaluated 110 RA patients, 88 (80%) women, 56 (%) under biologics, age 54±11 years, 14±10 years of disease duration, mean DAS28(4v) of 4.25±1.31. In a multivariate modelling (after adjusting for age, BMI, disease duration, average daily dose of prednisone, years of corticosteroid use and years of anti-repsortive therapy) and in RA patients exclusively under conventional DMARDs, moderate disease activity, according DAS28(4v), was associated with higher sclerostin levels (p<0.05). There was a trend for higher RANKL levels among severely active patients. DAS28(4v) was negatively associated with femoral neck (p<0.05), hands (p<0.001) and second proximal phalanges (p<0.005) BMD. Using the same model and adjusting also for years of biologic therapy, in the group under biologic agents, sclerostin levels were positively associated with disease activity (p<0.05). Higher DAS28(4v) values were associated with lower total hip, femoral neck, hands and second proximal phalanges BMD (p<0.001). Conclusions: In our RA population a strong negative association between disease activity and both hand and femoral BMD measurements was found. The link between high disease activity and increased sclerostin levels could represent a cause for decreased bone formation in active RA. Disclosure of Interest: None Declared